A protocol for in vitro production of microtubers in Chinese yam (Dioscorea opposita). Issue 6 (3rd June 2014) - Li, Mingjun; Li, Junhua; Liu, Wen; Liu, Luying; Lu, Jie; Niu, Jia; Liu, Xinying; Yang, Qingxiang
Abstract: Chinese yam ( Dioscorea opposita ) is an important tuberous crop owing to its dual use as a food as well as a medicine. Tissue culture techniques allow the rapid multiplication of virus-free plant materials. The use of microtubers offers an attractive alternative to in vitro -grown plantlets for the micropropagation and exchange of healthy Chinese yam materials. A protocol for the in vitro production of Chinese yam microtubers was developed in this study. Though we tested both one-step and two-step procedures, only the two-step procedure showed favorable results for tuberization. Media with 60 g L −1 sucrose yielded the highest microtuber index. We demonstrate that table sugar was an efficient and economical alternative to analytical grade sucrose for microtuber production. Using an orthogonal experimental design, we determined the optimal growth regulator combination for microtuber induction and development. The microtubers obtained from our protocol sprouted readily both in vitro and in soil. Graphical abstract: : In Vitro Production of Microtubers in Chinese yam and Sprouting Test. A Protocol for Efficient Microtuber Production was Developed in This Study.